Reasoned administration and democratic legitimacy how administrative law supports democratic government - Mashaw, Jerry L. (Cambridge University Press, 2018)
"Preface and Acknowledgements Critiques of administrative governance go back at least to the Jeffersonian Republicans' objections to the creation of the First Bank of the United States. And, like those early "Democrats" laments, critical commentary is often focused on a presumed democratic deficit. For many, countering the pernicious effects of "big government", and re-establishing democracy and the rule of law, entails returning lawmaking to Congress and the judiciary. These complaints continue unabated in the academic literature, judicial decisions and popular political discourse. For example, conservative legalists have embraced Philip Hamburger's book, "Is Administrative Law Unlawful?" (answer yes) notwithstanding Hamburger's thoroughgoing misunderstanding of both modern American administrative law, and the functioning of seventeenth century royal prerogative to which Hamburger compared our modern administrative jurisprudence. No less than the Chief Justice of the U.S. Supreme Court has weighed in with his own concerns the Americans now live in a gigantic and all-powerful administrative state. As these words are written multiple bills are before Congress that would, among other things, make all significant agency regulations ineffective unless specifically approved by Congress and instruct reviewing courts to give agency interpretations of their organic statutes no deference upon judicial review"--